Pencegahan Risiko Kecelakaan dan Kepatuhan Peraturan Keselamatan Kapal Pelayaran Internasional - Rahmad, Rikam; Sihombing, Sarinah; Sonny, Imam; Sijabat, Eduard Alfian Syamsya (Institut Transportasi dan Logistik Trisakti, 2024)
The purpose of the research is to find out the direct and indirect impact of the crew’s personal experience and safety training on preventing the accidental risk in compliance with shipping safety regulation of Abu Dhabi Maridive and Oil Services. Several problems found; the lack of ships’ crew awareness in compliance with the use of safety equipment when carrying out safety training and the lack of ships’ crew knowledge of the safe keeping and maintenance of the safety equipment. The study used a Path analysis with 60 samples of the Maridive and Oil Services Abu Dhabi crew. The study used linear regression analysis technique, simple correlation, partial and path analysis. The results state that the variable in compliance with safety regulations could mediate the safety training to prevent the accidental risk on board. It shows that good safety training could increase the prevention of on board accidental risk mediated by compliance of the safety regulation